2006
DOI: 10.1016/j.virol.2006.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of West Nile virus infectious DNA and its noninfectious derivatives

Abstract: The exceptionally high virulence of the West Nile NY99 strain makes its suitability in the development of a live WN vaccine uncertain. The aim of this study is to investigate the immunogenicity of noninfectious virus derivatives carrying pseudolethal mutations, which preclude virion formation without affecting preceding steps of the viral infectious cycle. When administered using DNA immunization, such constructs initiate an infectious cycle but cannot lead to a viremia. While the magnitude of the immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…In earlier reports, it had been demonstrated that mutants lacking the entire internal hydrophobic sequence of protein C are either severely impaired or not viable at all (21,42,44). Although this was also observed with some of the WNV deletion mutants analyzed in this study, the pseudorevertant ⌬36, lacking amino acids G40 to Q75 and thus the entire conserved hydrophobic domain, surprisingly demonstrates that efficient virion assembly and cell culture growth are in fact possible even in the complete absence of this region.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In earlier reports, it had been demonstrated that mutants lacking the entire internal hydrophobic sequence of protein C are either severely impaired or not viable at all (21,42,44). Although this was also observed with some of the WNV deletion mutants analyzed in this study, the pseudorevertant ⌬36, lacking amino acids G40 to Q75 and thus the entire conserved hydrophobic domain, surprisingly demonstrates that efficient virion assembly and cell culture growth are in fact possible even in the complete absence of this region.…”
Section: Discussionsupporting
confidence: 70%
“…Large deletions were tolerated only upon the acquisition of additional mutations increasing the hydrophobicity of the protein (21). These results are in good accordance with studies of YFV protein C (42) and WNV, in which case removal of the entire helix ␣2 produced a noninfectious phenotype (44). Furthermore, in DENV, removing large parts of the hydrophobic domain abolished both the ability to dimerize in vitro (46) and the ability to associate with the ER membrane (35).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The former is prone to introduction of undesired mutations, and the latter is not applicable for flaviviruses that do not replicate well in mice (e.g., dengue viruses). We and others have previously developed infectious cDNA clones for West Nile virus (WNV) and Japanese encephalitis virus (JEV) in which the in vitro RNA transcription step is eliminated by replacing SP6 or T7 polymerase promoters with the cytomegalovirus (CMV) promoter, thus allowing transcription of viral RNA in cells directly from plasmid DNAs by the cellular RNA polymerase II (16)(17)(18). Although an infectious cDNA clone for the Kunjin strain of West Nile virus (KUNV) has been demonstrated to be relatively stable, further manipulations, including mutagenesis could render it less stable (A. Khromykh, unpublished results).…”
mentioning
confidence: 99%
“…Although an infectious cDNA clone for the Kunjin strain of West Nile virus (KUNV) has been demonstrated to be relatively stable, further manipulations, including mutagenesis could render it less stable (A. Khromykh, unpublished results). To solve the problem of stability for CMV-based JEV and WNV infectious DNAs, the authors had to introduce introns into the viral genome (17,18). An additional modification of the infectious cDNA approach to eliminate potential instability was recently developed for rapid generation of WNV mutants in which DNA fragments harboring mutated structural genes were ligated in vitro with the genome in which structural genes had been deleted under the control of a CMV promoter, and the in vitro ligation reaction mixture was then directly transfected into mammalian cells to recover infectious viruses (19).…”
mentioning
confidence: 99%